PEMAJAKAN EKONOMI DIGITAL DI INDONESIA: TANTANGAN KONSEPTUAL DAN YURIDIS DALAM PENERAPAN SIGNIFICANT ECONOMIC PRESENCE - Hidayat, Agi Attaubah; Anwari, Amalia Nur; Sugiarti, Lilis Diah; Zulvia, Ransya Ayu; Najmudin, Nandang (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
The digital economy transformation challenges the relevance of the Permanent Establishment principle in Indonesia’s tax system. As a response, the Significant Economic Presence (SEP) concept was introduced to tax foreign digital entities without physical presence. This study aims to examine the conceptual and legal challenges in implementing SEP in Indonesia. The method used is normative-juridical with statutory and conceptual approaches. The findings reveal that SEP implementation faces legal uncertainty, conflicts between domestic and international norms, and lacks clear technical parameters. While SEP holds potential for promoting fiscal justice, its ambiguous legal basis risks creating discrimination unless supported by regulatory reform and international cooperation. This study highlights the urgency of harmonizing tax laws and strengthening institutional capacity to meet global digital taxation challenges.